2017
DOI: 10.1016/j.jenvp.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Seeing our self reflected in the world around us: The role of identity in making (natural) environments restorative

Abstract: Please cite this article as: Morton, T.A., van der Bles, A.M., Haslam, S.A., Seeing our self reflected in the world around us: The role of identity in making (natural) environments restorative, Journal of Environmental Psychology (2016Psychology ( ), doi: 10.1016Psychology ( /j.jenvp.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 63 publications
4
21
0
2
Order By: Relevance
“…Additionally, the researchers found that residents who were strongly identified with their neighbourhood had higher self-esteem,a finding which accords with previous studies that have examined the relationship between place-related identities and self-esteem (Knez, 2005;Fleury-Bahi & Marcouyeux, 2010;Twigger Ross & Uzzell, 1996). Along similar lines, other research informed by the social identity approach has shown that psychological wellbeing associated with restorative (Morton, van der Bles & Haslam, 2017), spiritual (Ysseldyk, Haslam, & Morton, 2016) and festive (Schmitt, Davies, Hung, & Wright, 2010) environments are shaped by social group identification.…”
Section: Social Identification Perceived Neighbourhood Quality and Msupporting
confidence: 81%
“…Additionally, the researchers found that residents who were strongly identified with their neighbourhood had higher self-esteem,a finding which accords with previous studies that have examined the relationship between place-related identities and self-esteem (Knez, 2005;Fleury-Bahi & Marcouyeux, 2010;Twigger Ross & Uzzell, 1996). Along similar lines, other research informed by the social identity approach has shown that psychological wellbeing associated with restorative (Morton, van der Bles & Haslam, 2017), spiritual (Ysseldyk, Haslam, & Morton, 2016) and festive (Schmitt, Davies, Hung, & Wright, 2010) environments are shaped by social group identification.…”
Section: Social Identification Perceived Neighbourhood Quality and Msupporting
confidence: 81%
“…In addition, surroundings that were meaningful to individuals also triggered positive responses. This supports the idea that the nature of therapeutic and restorative outcomes arising from interactions with environments is relational (Conradson, 2005) and the idea that restoration may be contingent on additional, personrelated factors, other than the intrinsic qualities of nature (Morton et al, 2017;Korpela, 2016, 2018;Bell et al, 2015;Ratcliffe et al, 2013). Four themes were identified as potential contributors to restoration in the urban setting.…”
Section: Discussionsupporting
confidence: 67%
“…Restoration researchers have -amongst others -attempted to chart the positive cognitive (for a review: Ohly et al, 2016), affective (for a review: McMahan & Estes, 2015) and psychophysiological effects of nature contact (e.g., Ulrich et al, 1991;Hartig, Evans, Jamner, Davis, & Gärling, 2003;Chang, Hammitt, Chen, Machnik, & Su, 2008;Van Den Berg & Custers, 2011). Efforts have been made to determine the optimal dose (Barton & Pretty, 2010;Shanahan et al, 2016) and modality (e.g., virtual versus real nature; Pals, Steg, Dontje, Siero, & van Der Zee, 2014) of nature for restoration, while research has also demonstrated how restorative nature effects can depend on group characteristics (e.g., elderly: Ottosson & Grahn, 2005;children: Taylor & Kuo, 2008;Ulset, Vitaro, Brendgen, Bekkhus, & Borge, 2017), on individuals' salient identities (e.g., Morton, van der Bles, & Haslam, 2017) or on the life stage one is in (Scopelliti & Giuliani, 2004).…”
Section: Nature's Broken Path To Restoration a Critical Look At Attementioning
confidence: 99%